(untitled) (Academic Journal of Internal Affairs, 2024)
In this paper, József Dakos responds to Ferenc Kodba’s claims that question the professionalism of the Baranya County Police Headquarters’ investigation. The author refutes Kodba’s assertions in detail, supporting them with specific facts and legal arguments.